Pro Visual Studio LightSwitch 2011 Development - Leung, Tim.; Duran, Yann.; SpringerLink (Online service) (Berkeley, CA : Apress, 2012)
Microsoft Visual Studio LightSwitch 2011 is a rapid application deployment tool that lets power users and administrators build data-centric business applications for the desktop, cloud, and Web in just a few clicks, with no code required. But more advanced developers and business users will hunger for more: how do you design complex screens? How do you query data using LINQ and other syntax structures? How do you secure your application? Pro Visual Studio LightSwitch 2011 Development answers these questions and more as authors Tim Leung and Yann Duran$1 (Bboth awarded Microsoft 2011 Community Contributor Awards for their LightSwitch expertise$1 (Bcover this breakthrough product and its operations and structure under the covers. For serious developers building, enhancing and deploying advanced business applications using LightSwitch, Pro Visual Studio LightSwitch 2011 Development is the guide for going beyond the "click-and-you're-done" interface, while still maintaining the elegance and convenience of rapid application development.s
Keywords: Computer science; Computer Science; Computer Science, general